Application of Various Biofertilizers on Vegetative Growth in Oil Palm Seedling - Krisnawati, Endang; Adirianto, Bayu; Bachtiar, Taufik (Syntax Corporation, 2024)
Continuous application of inorganic fertilizers has negative effects on the environment such as plants and soil. One of the efforts to reduce the use of inorganic fertilizers is the use of microbes as biological agents. This study aims to examine the effect of biofertilizer applications from brands A, B, C, and D on vegetative growth in oil palm seedling. This research was held at Bogor Agricultural Development Polytechnic. The study was arranged in a completely randomized design (CRD) followed by Duncan's test. The treatments consisted of 4 brands of biofertilizer with 3 doses (10, 20, and 30 mL/L water) and 8 replicates. The results showed that brand A had a significant effect on dry weight at a dose of 20 mL/L water with a dry weight value of 10.43 gram/plant. The highest root length significantly was the application of brand C at a dose of 20 mL/L of water, which was 39.06 cm/plant. However, the highest root volume significantly was fertilizer brand A with a dose of 10 mL/L of water, which was 12 cm3/plant.